Sherlock 3CGtip confirmation system for placement of peripherally inserted central catheters and related nursing countermeasures in a patient with double superior vena cava (1例双上腔静脉患者Sherlock 3CG尖端定位下经外周静脉穿刺中心静脉置管及护理对策) - SONG Lanna (宋兰娜); WANG Yuan (王媛); WANG Wenxuan (王文萱); WANG Yu (王钰); ZHANG Na (张娜) (中西医结合护理)
This paper summarized the experience of using Sherlock 3CG tip confirmation system for bilaterally placement of peripherally inserted central catheters (PICC) and related nursing countermeasures in a patient with double superior vena cava. In order to meet the treatment needs, PICC catheters were placed on both sides twice, with the catheter tips located in the right and left superior vena cava. The patient's first choice of the right upper arm for catheterization was smooth, and the second choice of the left side for catheterization was smooth. The Sherlock 3CG tip confirmation system was used for positioning. The P wave of the catheter sent to the reserved length continued to be negative. The results of computer tomography (CT) showed that the patient had permanent left superior vena cava. The X-ray positioning was performed to confirm that the tip of the catheter was located in the left superior vena cava. After comprehensive evaluation by the multidisciplinary team, the catheter indwelling length was adjusted, The patient's condition was closely observed, and health education was strengthened in many aspects. Indwelling catheter was successfully placement without complications. (本文总结了应用Sherlock 3CG尖端定位技术为1例急性髓系白血病伴有双侧上腔静脉患者双侧置入经外周静脉穿刺中心静脉导管(PICC)的护理对策。本例患者为满足治疗需求分别于两次经两侧置入PICC导管, 导管尖端分别位于右、左两侧上腔静脉。患者首次选择右侧上臂置管过程顺利, 再次置管选择左侧置入过程顺利, 应用Sherlock 3CG技术定位, 导管送至预留长度范围P波持续呈负波, 查看计算机断层扫描(CT)结果提示患者存在永存左上腔静脉, 行X光定位确认导管尖端位于左侧上腔静脉。经多学科团队综合评估, 调整导管留置长度, 密切观察患者情况, 加强多方面健康宣教, 导管留置成功, 无并发症发生。)